Ectopic adrenocortical adenoma in the renal hilum: a case report and literature review - Liu, Yang (Diagn Pathol, 2016)
BACKGROUND: Ectopic (accessory) adrenocortical tissue, also known as adrenal rests, is a developmental abnormality of the adrenal gland. The most common ectopic site is in close proximity to the adrenal glands and along the path of descent or migration of the gonads because of the close spatial relationship between the adrenocortical primordium and gonadal blastema during embryogenesis. Ectopic rests may undergo marked hyperplasia, and occasionally induce ectopic adrenocortical adenomas or carcinomas. CASE PRESENTATION: A 27-year-old Chinese female patient who presented with amenorrhea of 3 months duration underwent computed tomography urography after ultrasound revealed a solitary mass in the left renal hilum. Histologically, the prominent eosinophilic tumor cells formed an alveolar- or acinar-like configuration. The immunohistochemical profile (alpha-inhibin+, Melan-A+, synaptophysin+) indicated the adrenocortical origin of the tumor, diagnosed as ectopic adrenocortical adenoma. The patient was alive with no tumor recurrence or metastasis at the 3-month follow-up examination. CONCLUSIONS: The unusual histological appearance of ectopic adrenocortical adenoma may result in its misdiagnosis as oncocytoma or clear cell renal cell carcinoma, especially if the specimen is limited. This case provides a reminder to pathologists to be aware of atypical cases of this benign tumor. Although uncommon, an ectopic adrenal lesion should be included in the differential diagnosis of tumors involving the renal hilum. A misdiagnosis of this benign condition as a malignant renal tumor may have severe consequences for the patient, including unnecessary radical nephrectomy. Preoperative biopsy and appropriate immunohistochemical staining will assist in determining the origin and nature of the tumor and in avoiding intraoperative uncertainty.